Organizing a consortium of schools in Makati, Metro Manila a case presentation - Habulan, Nenita V. 1949-
Various procedures used in organizing a consortium of schools in Makati, Metro Manila were presented in this study. The insufficiency of educational media resources in some schools in Makati, the need for in-service training programs in educational media for teachers and media personnel, and the need to improve education through the adoption of innovative instructional methodologies and the extensive use of media resources are the bases for the organization of Makati Consortium.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: University cooperation -- Philippines -- Makati (Metro Manila).; Educational exchanges -- Philippines -- Makati (Metro Manila).; Media programs (Education).